Political elites and journalistic practices in India: A case of institutionalized heteronomy. (January 2021) - Maheshwari, Swati; Sparks, Colin
The national elections in India in 2014 that swept the controversial leader Narendra Modi to power have generated a great deal of scholarship on their transformative impact with regard to the Indian polity. This article argues that, in fact, the elections demonstrate a continuity in the media's relationship with dominant members of the political elite. Favourable, partisan reporting of dominant figures or families has a long history in India since the journalistic field reorients its subservience towards the new power structure. This research examines the similarities and differences in how authoritative and populist leaders like the Gandhis and Modi manipulate media power. While scholars have noted a close correspondence between politics and media in India, there is a research deficit in the analysis of the architecture of the media's subservience to selected members of national significance, in the world's largest democracy. This research draws into dialogue two influential theories – Field and New Institutionalism theory – to assert that the natural state of the Indian journalistic field is heteronomy in its relationship with hegemonic members of the political elite. This is occasionally pierced by limits imposed by populist politics in an electoral democracy. The relationship between the news media and individuals of the political elite, thus, can be conceptualized as that of contingent heteronomy.